Study on the Photoacoustic Technology to Simultaneous In-Situ Detection of the Cavity Ring-Down Spectrum for Multi-Optical Parameters - Hua-Wei Jin; Ren-Zhi Hu; Pin-Hua Xie; Chong-Chong Huang; Feng-Yang Wang; Chuan Lin (IEEE Photonics Journal)
A simultaneous in-situ detection technique to obtain multi-optical parameters was proposed. The same 403.56 nm, low power, blue diode laser was used to conduct the cavity ring-down spectroscopy and photoacoustic spectroscopy, which were coupled. Four photoacoustic spectra were applied to the simultaneous in-situ detection of the cavity ring-down spectrum, which were systematically compared and analyzed for the first time. And the main performance of the systems varied with the arrangement of the photoacoustic pool. The results reveal that the photoacoustic response was optimized by the high reflectivity mirror with the pool constant of 1450.64 (Pα·cm)/W and the signal sensitivity of 0.2562 μv/ppb. The intensity value of the photoacoustic pool inside the cavity ring down was superimposed to 48.45% of the initial intensity. The corresponding experimental results were consistent with the theoretical analysis and shown the coupled cavity could suitable for simultaneous in-situ measurement of high concentration. The coupled two detection techniques detected different optical parameters and thus provided a new method for the simultaneous in-situ detection of the multi-optical parameters of specific atmospheric components.